Herlyn-Werner-Wunderlich Syndrome: A Mini-review - Jiwon M. Lee (Korean Society of Pediatric Nephrology, 2018)
Herlyn-Werner-Wunderlich (HWW) syndrome is a rare congenital malformation syndrome that is characterized by a triad of uterine didelphys, blind hemivagina, and ipsilateral renal agenesis. There is a wide variety of phenotypic presentation which is recognized as a spectrum of disease rather than a separate entity. The exact incidence and pathogenesis of HWW syndrome are yet to be investigated. While this disease typically involves adolescent girls who present with abdominal pain or a pelvic mass that is secondary to hematocolpos, nowadays, a majority of potential patients with HWW are being prenatally screened for renal anomalies. Therefore, it is recommended to search for uterovaginal anomalies whenever a multicystic dysplastic kidney or the absence of a kidney is noted in a newborn female, and the role of pediatric nephrologists has become ever more important for early recognition of the disease.